Pengaruh Latihan Aerobic Class dan Body Language terhadap Penurunan Persentase Lemak Tubuh - Permana, Dhias Fajar Widya (Media Ilmu Keolahragaan Indonesia, 2014)
of exercise Aerobic classes, Body Language and joint exercises between Aerobic classes and body language to decrease body fat percentage. This study populations all participants gymnasium Astuti Studio Dance Semarang, amounting to 22 people. Total sampling sampling techniques namely: 7 aerobic exercise class, 7 and 8 the body language to follow aerobic classes and body language. The variables in this study consisted of a free variable that aerobics class, body language, aerobic classes and body language and the dependent variable is the percentage of body fat. Analysis of data using statistical techniques t-test. Based on the results obtained by t test, a significant decline in the percentage of fat sample after following aerobic gymnastics class (t = 7.49> table = 2.45); gymnastics body language (t = 5.28> table = 2.45); aerobic gymnastics class and body language (t = 7.15> table = 2.36). Conclusion: There is a clas Aerobic exercise effect, exercise body language and joint exercises between Aerobic classes and body language to decrease body fat percentage in the participants gymnasium Astuti Studio Dance Semarang.